RETRACTED: The Influence Of Service Quality, Company Image And Consumer Trust On Customer Satisfaction Pt. Indonesian Commuter Trains - Deby Dharmawan; Herry Krisnandi; Kumba Digdowiseiso (Journal of Social Science, 2024)
This study aims to analyze the effect of service quality, company image and consumer confidence on consumer satisfaction. In this study using primary data obtained from distributing questionnaires to 100 KRL transportation service customers at PT. Kereta Commuter Indonesia. This research uses descriptive analysis and inferential analysis, and analyzed using multiple linear regression correlation analysis, the model feasibility test, and hypothesis testing. The results of this study indicate that there is a positive and significant effect on customer satisfaction. The results of the multiple linear regression equation are Y = 0.672 + 0.211X1 + 0.245X2 + 0.278X3 The feasibility test of the model in the R2 test shows that service quality, company image and consumer trust have an effect of 59.2% on consumer satisfaction. In the results of hypothesis testing (t test) obtained a significant value on the quality of service veriabel of 0.001, a significant value on the corporate image variable of 0.005, and a significant value of consumer trust variables of 0.004, it can be concluded that it means partially the three independent variables have a positive influence and Significant to the dependent variable is the variable customer satisfaction at PT. Kereta Commuter Indonesia.